Thermoluminescence of Cu doped ZnS nanoparticles - Wanjari, Lata; Bisen, D P; Bramhe, Nameeta; Sharma, Ravi; Sahu, Ishwar Prasad (Recent Research in Science and Technology, 2012)
ZnS nanoparticles doped with Cu were synthesized by wet chemical route method at 4°C temperature. We have investigated the Thermoluminescence (TL) properties of the undoped ZnS and Cu doped ZnS with increase in Cu concentration from 0.5 millimole to 1.5 millimole and also study for different weight of Sodium Hexa Meta Phosphate (SHMP) capping agent from 2gm to 10gm. The XRD studies indicate that most of the samples are cubic in nature. The broadening of peaks tends to increase with increasing weight of capping agent showing decrease in particle size. The crystalline size computed using Scherer formula is found 2nm to 3nm. Absorption spectra show blue shift with different weight of capping agent. TL glow curve shows a single peak at 543 K temperature. Variation in TL intensity as a function of copper concentration is studied and 1mM is found to be the optimum concentration for TL. The trap parameters namely, activation energy (E), order of kinetics (b) and frequency factor(s) of ZnS: Cu sample have been determined using Chen’s method. The effect of heating rates and UV radiation dose for different time on TL glow curve has also been studied.